FACTORS AFFECTING THE MAKING ABILITY OF SME FINANCIAL REPORT IN THE OFFICE OF COOPERATIVES AND SMEs IN MEDAN - Lambok Manurung (Enrichment : Journal of Management, 2021)
This research was conducted at the Department of Cooperatives and SMEs Medan with the aim of research to determine the Factors affecting the making ability of SMEs financial reports in the office of cooperatives and SNEs in Medan. The factors that are being used in this research are the education level, socialization and information, knowledge of accounting, business size, and its length of time. Author is using the quantitative descriptive research type in this research. The population refers to the 3,637 SMEs and samples that were took is a total of 100 respondents. Data collection techniques that are being used here is surveys and data analysis techniques with multiple linear regression, classic assumption test, and test the feasibility. The results of this study showed that education level does not significantly affecting the making ability of SMEs financial report. While socialization and information, accounting knowledge, and size of the business and its length of time do have a significant effect on the Department of Cooperative SME Medan.